Penetapan Kadar Metronidazole dalam Sediaan Tablet Secara Spektrofotometri Infra Merah - Jimmi J (Herbal Medicine Journal, 2022)
Metronidazole is a type of antibiotic that has been widely used since 1960, and has been shown to be active against various anaerobic bacteria in vitro and experimental infections. According to Law Number 36 of 2009 concerning Health in paragraph 1 of article 105, it is stated that pharmaceutical preparations in the form of drugs and medicinal raw materials must meet the requirements of the Indonesian Pharmacopoeia or other standard books. The purpose of this study was to determine the concentration of metronidazole in tablets with trade names and generics and to determine the conformity of the levels to the requirements of the Indonesian Pharmacopoeia. Determination of paracetamol levels by Fourier Transform Infra Red (FTIR) Spectrophotometry using methanol solvent in the range of wave numbers 400 – 4000 cm-1. The results showed that the concentration of metronidazole in Novagyl® tablets (97.45 ± 0.36)%; Trichodazole® tablets (97.41 0.36)%; Metronidazole® tablets (94.42 0.40)%; Omenizole® tablets (99.07 0.13)%; Farizol® tablets (92.12 1.39)%. From the validation of the method carried out, the results of the recovery test were 100.9%, RSD 0.07%, and had LOD and LOQ of 3.3351 mg/mL and 11.1110 mg/mL respectively. These results indicate that the method used shows accurate and thorough results. The results of the study concluded that the determination of metronidazole levels could be carried out using Fourier Transform Infra Red (FTIR) spectrophotometry and the levels of metronidazole tablets met the requirements.